Effect of High-intensity Intermittent Training Program on Mood State in Overweight/Obese Young Men - Nejmeddine OUERGHI; Okba SELMI; Wissam BEN KHALIFA; Mohamed Kacem BEN FRADJ; Moncef FEKI; Naziha KAABACHI; Anissa BOUASSIDA (Tehran University of Medical Sciences, 2016)
No Abstract.